2014
DOI: 10.1039/c3tc31984a
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline radicals: discotic behavior of unsymmetrical derivatives of 1,3,5-triphenyl-6-oxoverdazyl

Abstract: A series of six 6-oxoverdazyl (1[10]) substituted with a total of three 3,4,5-tri(decyloxy)phenyl and/or 3,4,5-tri(decylsulfanyl)phenyl groups was investigated by thermal, XRD, spectroscopic, magnetic and photovoltaic methods. The compounds exhibit columnar hexagonal (1[10]c, Col h ), columnar hexagonal ordered (1[10]b, Col h(o) ), columnar hexagonal 3D (1[10]a, 1[10]e and 1[10]f, Col h(3D) ) or a sequence of two phases (1[10]b, Col h -Col h(3D) ). The mesophase structure and stability and also thermochromism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…This small bathochromic shift between the Iso and Col h phases is typical for other discotic verdazyls. [14] Upon cooling of the sample from Iso to Col h(o) phase, λ max changes in the opposite direction with about 5 K hysteresis ( Figure 4). …”
Section: Liquid Crystals 1655mentioning
confidence: 95%
See 2 more Smart Citations
“…This small bathochromic shift between the Iso and Col h phases is typical for other discotic verdazyls. [14] Upon cooling of the sample from Iso to Col h(o) phase, λ max changes in the opposite direction with about 5 K hysteresis ( Figure 4). …”
Section: Liquid Crystals 1655mentioning
confidence: 95%
“…[11] Recently, we demonstrated that substituted triphenyl derivatives of verdazyl, a π-delocalised radical, form discotic hexagonal phases. [12][13][14] We have investigated three series of compounds containing 3,4,5-trialkoxyphenyl [12] (such as 1a), 3,4,5-trialkylsulfanylphenyl [13] and a mixture of both substituents. [14] The results demonstrated that the alkylsulfanyl derivatives form a disordered columnar hexagonal 3D phase (Col h(3D) ) below 60°C, presumably with a helical structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of recent papers, 1,3,5-trisubstituted 6-oxoverdazyl radical has been demonstrated as an effective structural element for both disc-like [1][2][3][4] and bent-core [5] liquid crystalline materials. Whereas the former class of compounds exhibit columnar phases exclusively (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Materials based on p-delocalized radicals are of particular interest in the context of molecular electronics and spintronics 2 due to their photophysical and electrochemical properties. 3 In this context we have been working with 6-oxoverdazyl and demonstrated that it is a suitable paramagnetic structural element for disc-like [4][5][6][7][8][9] and bent-core, such as 1[n] (Fig. 1), 10,11 liquid crystalline materials.…”
Section: Introductionmentioning
confidence: 99%